A multidimensional analysis of metadiscourse markers across written registers. (April 2016) - Zhang, Man
The existing metadiscourse studies have focused on relatively specific registers. Metadiscourse in written and/or spoken registers in general has received little attention. To explain more fully the nature of metadiscourse, this article undertakes a comprehensive linguistic analysis of metadiscourse markers in written registers based on a reflexive model of metadiscourse. Specifically, this article conducts a multidimensional analysis of register variation of metadiscourse markers across the press, general prose, academic prose and fiction in the Freiburg update of the Lancaster-Oslo/Bergen Corpus of British English (500 texts; 1, 000, 000 words). Three Metadiscourse Dimensions are extracted and interpreted: writer presence, text presentation and reader guidance. Mean dimension scores are computed as a basis for functional interpretation of register variation. Results show that the appropriate use of metadiscourse markers crucially depends on the register. Metadiscourse markers are more pervasive in more informational and abstract registers (academic, general prose, editorials), especially for the function of text presentation. On the contrary, metadiscourse markers are rare in narrative and concrete registers (fiction, press, reportage), and are mostly used for the purpose of reader guidance.